2015
DOI: 10.1016/j.desal.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced energy generation and membrane performance by two-stage pressure retarded osmosis (PRO)

Abstract: Power density, extractable energy and average power density are introduced.• Four different configurations of the proposed TwoPRO are proposed and analyzed.• CDCF, CDDF and DDCF have advantageous osmotic energy capacity.• At high dimensionless flow rate, CDCF and CDDF have high average power density. a b s t r a c tA systematic model of a salinity power plant involving two PRO (TwoPRO) modules is presented in this paper. The results clearly indicate that the performance of a PRO plant can be improved with a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Shaheed et al [25] introduced dual stage PRO system and conducted a thermodynamic analysis on it. In another study, they proposed four configurations of CDCF, DDDF, CDDF, and DDCF, either with the continuous or divided flow (C or D) of the draw and feed solution (D and F) ( Figure 2.16) [129]. All configurations utilize energy recovery systems and pump-turbine (PT) pairs.…”
Section: Dual Stage Pro Systemsmentioning
confidence: 99%
“…Shaheed et al [25] introduced dual stage PRO system and conducted a thermodynamic analysis on it. In another study, they proposed four configurations of CDCF, DDDF, CDDF, and DDCF, either with the continuous or divided flow (C or D) of the draw and feed solution (D and F) ( Figure 2.16) [129]. All configurations utilize energy recovery systems and pump-turbine (PT) pairs.…”
Section: Dual Stage Pro Systemsmentioning
confidence: 99%
“…Practically, this reduces the efficiency of PRO process and makes its application less productive. Recent research has suggested adding a second stage PRO process to capture the rest of osmotic energy from the diluted draw solution before discharge [25][26][27], hence maximizing the energy efficiency of PRO process. The diluted draw solution from the first stage and a raw feed solution are coupled to form the salinity gradient of the second stage [ Figure 1]; this will rebuild the chemical potential difference across the PRO membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an energy and thermodynamic analysis of the single-stage PRO process was conducted by He et al [62], and further, the performance of the dual-stage PRO process under four different configurations was identified [63]. It was found that the configurations of the continuous draw and continuous feed solution (CDCF) and the continuous draw and divided feed solution (CDDF) were more beneficial than for single-stage PRO processes.…”
Section: Numerical Studies Regarding Promentioning
confidence: 99%